Greener NTU campus : pollution diagnostics of campus infrastructure - Wong, Zhi Bin (2017)
Methods of dust samples collection varies for different experimental setups. In this project, the collection of dust samples was chosen specifically by using filter papers to collect the dust samples so as to obtain the optimum result due to the higher concentrations of dust samples collected. Dust samples were analyzed to determine the heavy metals concentration in the dust collected from the Nanyang Technological University (NTU) campus. Dust samples were obtained from the notice board at a bus stop and the ventilation hood in the laboratory in campus. This project aims to determine the different heavy metals present in the environment within the campus and whether the concentration levels exceed the maximum concentration permissible.